Pengaruh Harga, Promosi dan Kualitas Pelayanan terhadap Kepuasan Pengunjung di Wisata Pemandian Air Panas So’a Mengeruda Kabupaten Ngada - Mau Daa, Maria Gravasia; Riwu Manu, Rolens E.H; Saragih, Fernando (Journal Economic Education, Business and Accounting, 2026)
This research aims to find out how visitor satisfaction at the So'a Hot Springs Tourism is influenced by price, promotion and service quality. The type of research used in this research is quantitative research with a population taken historically or with monthly reports of 150 visitors. In this study, the sample taken was 70 respondents taken using the incidental sampling technique. The data collection techniques used are documentation and questionnaires. Multiple linear regression, t test, F test, classical assumption test, and efficiency of determination are some examples of data analysis techniques used in this quantitative research. Based on the calculation of the F test results, it can be seen that the calculated F value obtained is 93,268 which is greater than the F table (93,268 > 2.74) and the significant value is 0.000 (0.000 < 0.005) so it can be concluded that H4 is accepted which states that it is suspected that there is an influence between price, promotion and service quality on visitor satisfaction at the So'a Mengeruda Hot Springs Tourism, Ngada Regency.